Iodine‐mediated oxidation of resveratrol. An electroanalytical study using platinum and glassy carbon electrodes - Gómez-Monedero, B; Jiménez-Pérez, R; González-Sánchez, M; Almagro, L; Valero, E; Compton, R (Wiley, 2019)
Resveratrol is a phenolic compound that shows important biological antioxidant activities. In this paper, the electrochemical oxidation of iodide in the presence of resveratrol was investigated using both platinum and glassy carbon electrodes. The experimental results showed a diffusion controlled process for the oxidation of iodide to iodine, followed by the chemical reaction of iodine with resveratrol. The possible applicability of iodine-mediated reaction in the quantitative analysis of resveratrol was studied, obtaining sensitivities of 0.98±0.03 and 4.22±0.20 μAμM −1 cm −2 using platinum and glassy carbon electrodes, respectively. The resveratrol content in a sample obtained from the extracellular medium of elicited suspension-cultured cells of Vitis vinifera was evaluated and compared with data obtained by HPLC analysis, with good correlations. The signal of other compounds that may be present in the samples or they are precursors of the biosynthesis of trans-resveratrol (L-ascorbic, glycine, saccharose, tyrosine, cinnamic acid and p-coumaric acid) was also evaluated, which shows lower interferences when using glassy carbon electrodes.